The Effect of Tele-nursing on Preventing Re-admission among Patients with Heart Failure: A Literature Review - Effita Piscesiana; Tuti Afriyani (Alta Dharma Publisher, 2020)
Nurses have a role as educators. The purpose of the nurse is to help the client to learn about his condition and what health service procedures must be undertaken to maintain his health status. Tele nursing is a method of communication in providing education to clients, especially clients with heart failure. This literature study seeks to describe how to implement effective telenursing in patients with heart failure. Several databases were collected from the following sources: Science Direct, ProQuest, Scopus, EBSCO, BMJ, Research Gate, Clinical Key, articles collected have conditions for publication between 2014 - 2019 and selected based on compatibility with keywords. Knowledge and ability of efficient telephone communication from nurses should be enhanced to be tailored to the needs of patients. It was combined with comprehensive systematic monitoring that can be used in building professional relationships between clients and nurses, making implementation easier. Tele nursing methods can be developed to find better ways to communicate with patients after the hospitalization process to prevent clients from returning to the hospital. Tele nursing cannot work alone but requires an integrated system to support telemonitoring so that clients can be monitored on an ongoing basis to maintain their health status